Nutritional, nutraceutical attributes, microbiological and chemical safety of different varieties of dates—A review - Ibrahim, Aimie Syahirah; Sukor, Rashidah; Anwar, Farooq; Murugesu, Suganya; Selamat, Jinap; Raseetha, Siva (Elsevier B.V., 2024)
Dates are valued as a highly nutritious food with multiple nutraceutical properties. Date fruits are widely consumed, especially in the Middle Eastern regions. Dates are a vital source of readily metabolisable natural sugars, minerals, vitamins, dietary fibre, protein, and other high-value natural antioxidant compounds such as carotenoids and phenolics. Nutritional and nutraceutical composition and properties of dates vary according to variety, origin, fruit maturity level, and post-harvest processing conditions. Dates, like many other fruits, are susceptible to microbial contamination, particularly during improper pre- and post-harvest handling and storage. The prevalence of mycotoxin and bacterial contamination not only spoils the functional food quality of dates nevertheless it poses potential adverse effects on human health. With increased interest in the health benefits of dates, there is a greater need to examine and understand potential microbiological safety issues linked with commercial dates. The main goal of this review is to present comprehensive and most up-to-date scientific findings about the high-value components profile, nutritional and nutraceutical qualities, and microbiological safety of various types of dates consumed around the world. Furthermore, the study urges innovative mitigation strategies to combat microbial contamination while maintaining the safety and quality of dates supplied and consumed as part of the food chain.